Squaring the round: An unusual progressive graphomotor impairment with post‐mortem findings. Issue 2 (12th September 2015) - Code, Chris; Tree, Jeremy J.; Mariën, Peter
Abstract : Investigations of neurodegenerative disorders may reveal functional relationships in the cognitive system. C.S. was a 63‐year‐old right‐handed man with post‐mortem confirmed Pick's disease with a range of progressive impairments including non‐fluent aphasia, speech, limb, oculomotor, and buccofacial apraxia, but mostly intact intelligence, perception, orientation, memory, semantics, and phonology. During progression, agrammatism in writing with impairments in syntactic comprehension emerged in parallel with an unusual graphomotor deficit in drawing and writing, with an increasing deterioration of graphic short‐term memory. We investigated C.S.'s graphomotor deficit longitudinally using tests of writing and drawing on letters, words, and sentences and drawing to command and copying. We also tested C.S.'s short‐term graphemic buffer experimentally. Analysis showed deficits on selective aspects of graphomotor implementation of writing and drawing, mainly affecting the production of circles and curves, but not short straight lines in drawing and writing, and graphomotor short‐term memory, which paralleled impairments of written syntax and syntactic comprehension. We believe this to be the first detailed analysis of such an unusual progressive impairment in graphomotor production, which may be related to problems with agrammatic agraphia and impairments affecting shared components of cognition reflecting damage to shared neural networks. Alternatively, they may simply reflect the effects of coincidental damage to separate mechanisms responsible for aspects of writing, drawing, and syntactic processing. Longitudinal investigations of emerging deficits in progressive conditions like C.S.'s provides an opportunity to examine the progressive emergence of symptoms in an individual with multiple progressive impairments as they appear and examine putative relationships between them.